Moisture Sorption Isotherms and Drying Kinetics of Lepironia articulata: Effects of Hot Air Drying on Mechanical Properties and Structural Changes - Chankuson, Pitchasak; Pethuan, Sirikun; Yuennan, Jureeporn; Kaew-on, Surasak; Kaew-on, Chaiporn (Trends in Sciences, 2026)
This study systematically investigates the moisture sorption behavior, drying kinetics, and coupled structural-mechanical responses of Lepironia articulata (LA) fiber under controlled hot-air drying conditions (40 - 80 °C). Equilibrium moisture content (EMC) was determined at water activity levels ranging from 0.1 to 0.9 and modeled using several empirical equations. Among these, the Modified Guggenheim-Anderson-de Boer (GAB) model provided the best fit across all temperatures, exhibiting the highest coefficient of determination (R²) and lowest root mean square error (RMSE), indicating its suitability for describing sorption behavior in lignocellulosic fibers. Drying kinetics were analyzed using nine thin-layer drying models, where the Modified Page model consistently demonstrated superior predictive accuracy. The drying process was dominated by the falling-rate period, confirming that internal moisture diffusion governs mass transfer. Increasing drying temperature significantly accelerated moisture removal, reducing the drying time required to reach a moisture ratio of 0.10 from approximately 540 min at 40 °C to 140 min at 80 °C. Mechanical testing revealed a non-linear dependence of tensile strength on temperature, with an initial reduction at 40 - 50 °C, followed by recovery at 60 - 70 °C, and a maximum value at 80 °C, while elongation at break remained relatively stable. FTIR analysis indicated progressive dehydration, reduction of hydroxyl groups, and degradation of hemicellulose, accompanied by increased cellulose ordering. SEM observations confirmed corresponding morphological changes, including fiber densification at moderate temperatures and micro-crack formation and cell wall collapse at higher temperatures. The apparent contradiction between increased tensile strength and structural damage at elevated temperatures is explained by crystallinity-driven stiffening and improved microfibril alignment, which dominate bulk mechanical behavior despite localized defects. Overall, drying at 60 °C was identified as the optimal condition, providing a balance between efficient moisture removal, mechanical performance, and structural integrity. These findings provide a comprehensive framework for optimizing drying processes and enhancing the utilization of natural lignocellulosic fibers in sustainable material applications. HIGHLIGHTS Modified GAB model accurately predicts EMC of Lepironia articulata fiber across aw 0.1 - 0.9. The modified Page model best describes drying kinetics dominated by internal moisture diffusion. Drying temperature significantly affects structure-property relationships, with tensile strength peaking at 80 °C due to increased cellulose crystallinity. The optimal drying condition is 60 °C, balancing moisture removal efficiency, mechanical performance, and structural integrity. GRAPHICAL ABSTRACT